2020
DOI: 10.1109/access.2020.3033004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hypertensive Patients With Higher Risk of Developing Vascular Events Using Heart Rate Variability and Machine Learning

Abstract: The prognosis of cardiovascular and cerebrovascular events for patients suffering from hypertension is considered of a high importance in preventing any further development of cardiac diseases. Despite of the ability of current gold standard techniques in predicting vascular events risks, they still lack the required clinical efficiency. In this vein, the study proposed herein provides an investigation on the feasibility of using heart rate variability (HRV) utilized through a machine learning approach to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 45 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…Afterward, SRC-AL presented herein was compared with SRC and some popular models of TSC, including 1NN-DTW, random forest (RF), and support vector machine (SVM). Due to the limited samples, the leave-one-out cross-validation was adopted to carry out the experiments [ 52 ]. All the above models were implemented by MATLAB.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Afterward, SRC-AL presented herein was compared with SRC and some popular models of TSC, including 1NN-DTW, random forest (RF), and support vector machine (SVM). Due to the limited samples, the leave-one-out cross-validation was adopted to carry out the experiments [ 52 ]. All the above models were implemented by MATLAB.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…In general, works conducted using ML and DL coupled with ECG signals have yielded the highest and optimum performance. The works done in Table 2 , Table 3 and Table 4 , 2 , 8 , 13 , 16 , 21 , 23 , 24 , 25 , 26 , 34 , 35 , 26 ] have used public (open source) databases, while the rest of the studies have used private databases. This underscores the importance of public databases for computer aided diagnosis systems development.…”
Section: Discussionmentioning
confidence: 99%
“…HRV signals extracted from SHAREE were used in [ 13 , 16 , 26 ]. In [ 27 ], HRV signal derived from 10-min ECG recordings from 568 subjects were studied.…”
Section: Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have observed a strong association between HRV and cardiovascular diseases including CAD [15][16][17][18][19][20][21] . Specific cardiac function characteristics observed using different HRV features at certain times of the day/night cycle could suggest changes in cardiac function associated with heart failure progression in parallel with circadian rhythm changes.…”
Section: Introductionmentioning
confidence: 99%